Miniinvazivní osteosyntéza poranění pánve: CT studie rozměrů skeletu pánve - Džupa, Valér; Němec, Jan; Pavlíčko, Z; Laboš, Marek; Šrám, Jaroslav; Taller, Stanislav; Báča, Václav (Acta chirurgiae orthopaedicae et traumatologiae Čechoslovaca, 2016)
UNLABELLED: PURPOSE OF THE STUDY This radiographic study was focused on measuring the dimensions of pelvic bones at sites of minimally invasive screw insertion with the aim to assess the risk of damage to vascular and nervous structures. MATERIAL AND METHODS The group consisted of 77 patients (39 women and 38 men) aged between 19 and 85 years (average, 65; women, 65; men, 64) who underwent CT examination of the pelvis because of reasons other than injury. On the left side, a total of 14 dimensions of the superior pubic ramus, supraacetabular region, retroacetabular region, quadrilateral surface of the acetabulum and lateral foraminal sides of the S1 and S2 vertebral bodies were measured. The results were evaluated using descriptive statistics. RESULTS The inner antero-posterior dimension of the isthmic area of the superior pubic ramus was 8 mm or less in four women (10.3%) and 9 or 10 mm in further 14 women (35.9%). The inner cranio-caudal dimension of the superior pubic ramus was 8 mm or less in 14 women (35.9%) and 9 or 10 mm in further 16 women (41.0%). These dimensions obtained in men were as follows: 8 mm and less in three men (7.9%) (7 mm in one, 8 mm in two), and 9 or 10 mm in nine men. Sizes of the other pelvic bones were large enough to allow for safe insertion of single screws. DISCUSSION Single screws most frequently used in minimally invasive treatment of pelvic fractures are cannulated screws 7.3 mm or 6.5 mm in diameter; less frequently used are 4.5-mm cancellous screws (e.g. in treatment of avulsion injuries) or long 3.5-mm cortical "creeping" screws to be inserted in the superior pubic ramus. The use of "creeping" screws reported by several authors indicates problems associated with placement of standard screws (diameter, 7.3 mm and 6.5 mm) through the isthmus into the superior ramus. In slim high pelvises of some patients with gracile skeletons or in low pelvises of small women, the screws can protrude over the cortical margin. However, the risk of injury to nervous or vascular structures is low when the intraosseous screw is exactly inserted and it is so even in case its thread cuts into cortical bone. Neither the femoral artery nor the femoral nerve is situated too close to the superior pubic ramus. The "corona mortis" may potentially be jeopardised because of its contact with both the superior and posterior cortical bones of the superior ramus, but it usually follows a course more lateral to the isthmus of the ramus. CONCLUSIONS The results of the study showed that the size of the superior pubic ramus in its isthmic area may cause difficulties during insertion of cannulated screws with standard diameters (7.3 mm and 6.5 mm) in the majority of women and in some men. The risk of damage to vascular and nervous structures during screw insertion is associated only with the superior and posterior walls of the superior pubic ramus and with the area of the S2 foramen in case the correct procedure of intraosseous screw insertion is not strictly followed. KEY WORDS: retrograde pubic screw, iliosacral screw, supraacetabular screw, retrograde posterior column screw.
Keywords: Bone Screws; Fracture Fixation, Internal; Aged; Treatment Outcome; Minimally Invasive Surgical Procedures; Aged, 80 and over; lidé středního věku; senioři; vnitřní fixace fraktury; lidé; Adult; miniinvazivní chirurgické výkony; Middle Aged; dospělí; fraktury kostí; Fractures, Bone; Female; výsledek terapie; senioři nad 80 let; Male; ženské pohlaví; Pelvic Bones; mladý dospělý; Humans; mužské pohlaví; Young Adult; kostní šrouby; pánevní kosti